Efecto de Pseudomonas spp fluorescentes con actividad antagonista hacia Meloidogyne spp en el cultivo de tomate (Lycopersicum esculentum). - Valarezo Castro, Ronald Hernán (2017)
The constant application of nematicides for the control of M. incognita, has caused loss of beneficial microorganisms and environmental pollution. It is of biological control in agriculture is an alternative that benefits the physiological aspects of the plants and at the same time reducing the use of nematicides. This work aimed to evaluate rhizobacteria Pseudomonas fluorescent spp with antagonistic activity to Meloidogyne spp. in the tomato crop. The M. incognita in tomato plants reproduced by two months in greenhouse conditions. For morphological identification nematodes in different stadiums were recovered through the sieving. In molecular identification, DNA was extracted from roots with symptoms of damping with the help of QIAGEN kit and used two pairs of first Finc/Rinc and Inc-K14F / Inc-K14R with an amplification of 1200 and 399 pb. Seven strains of Pseudomonas that produce cyanide was used for the evaluation of the trials of hydrogen (HCN), protease, Pirrolnitrina, and catalase. We studied a single factor, rhizobacteria, were performed in vitro assays: 1) inhibition of M. incognita eggs hatch, the percentage was determined by counting 50 eggs per 0.5 cm2; (2) mortality of the M. incognita J2 evaluating strains to 4%. In vivo tests: plant height, root weight, number of galls, galls weight and population of the M. incognita J2. The design was used completely lift (D.C.A) to evaluate the antagonistic effect of rhizobacteria, Tukey's test was used to 95%. Strains p. protegens CHA0 and p. fluorescens PM3-8 showed more antagonistic activity towards M. incognita in the in vivo tests. Strains p. protegens CHA0, p. veronii R4, p. fluorescens BMR2-12 and PM3-14 showed greater antagonist activity in vivo assessments. Keywords: Meloidogyne incognita, rhizobacteria, antagonistic activity.